Membangun Kredibilitas Influencer Instagram: Efek Sikap dan Respon Perilaku Followers terhadap Influencer - Pratami, Aurora Alya Nurjihan; Astuti, Budi (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the credibility of Instagram influencers and their impact on followers' attitudes and behavior towards influencers. The approach used in this research is a quantitative approach. The respondents in this research were 190 people who had Instagram accounts and were followers of the famous Indonesian influencer account on Instagram, namely Fuji (@fuji_an). The type of data used is primary data obtained from respondent questionnaires. Data analysis was carried out descriptively and statistical testing using computer assistance from the SEM Partial Least Square (PLS) program. The research conclusion shows that product influencer suitability has a positive and significant effect on Influencer Motive Inference and Credibility, but influencer suitability has no influence on attitudes towards influencers. Motive inference has a positive and significant influence on ad recognition, ad recognition has a positive and significant influence on influencer credibility and attitudes towards influencers. The influence of influencer credibility on intention, shows that influencer credibility has no influence on intention to follow an account. Influencer credibility has no influence on the intention to imitate the influencer, and influencer credibility has a positive and significant influence on the intention to recommend the influencer. The influence of attitudes towards Influencers on followers' intentions to continue following, imitating, and recommending influencers found that attitudes towards influencers have a positive and significant influence on intentions to follow accounts, attitudes towards influencers have a positive and significant influence on intentions to imitate influencers, and attitudes towards influencers has a positive and significant influence on the intention to recommend influencers.